Penguatan Wawasan Kebangsaan dan Soft Skill Mahasiswa ADik melalui Pendampingan Partisipatif Reflektif - M. Yunasri Ridhoh; Nur Fadilah Ayu Sandira; Indri Iswardhani; Nulthazam Sarah; Sri Astuti Nasir (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2026)
This community service program aimed to strengthen national insight and soft skills among ADik scholarship students through a participatory and reflective mentoring approach. Many students come from underdeveloped, frontier, and outermost regions with diverse socio-cultural backgrounds, requiring contextual guidance to internalize national values and develop essential interpersonal competencies. The program combined interactive socialization, group discussions, and value reflection activities to encourage active participation and personal engagement. The method emphasized dialogic learning rather than one-way lectures, allowing students to relate national values to their lived experiences. The findings revealed noticeable behavioral changes, including increased confidence in expressing opinions, stronger participation in discussions, improved communication skills, and heightened awareness of ethical conduct and financial responsibility as scholarship recipients. The emergence of several students as informal local leaders during discussions indicated early signs of social transformation at the individual level. This program demonstrates that reflective and participatory mentoring can effectively foster character building, leadership, and contextual national awareness among university students. The implications suggest that similar approaches can be adopted in student development programs to promote sustainable character formation, especially for students from diverse and remote regions.